Influence of alloy chemistry on the transformation temperatures and local atomic structure of shape memory alloys : with a focus on NiTi-based intermetallics - Mehrdad Zarinejad (2009)
The dependence of transformation temperatures of shape memory alloys on the number and concentration of valence electrons are studied. This dependence is further analyzed for NiTi-based alloys followed by an investigation of the effect of precipitation on the Ms temperature, and the influence of composition change on the local atomic structure and transformation temperature of NiTiHf alloys. The bond evolution and change of transformation temperature during the local chemistry change of a Ni25Ti50Cu25 melt-spun ribbon during crystallization is also studied. The shape memory alloys are categorized into low (ev/a<5), medium (5≤ev/a≤7.50), and high (ev/a>7.50) valence electron groups. For majority of alloys in medium and high valence electron group, clear correlations between transformation temperatures and their valence electron concentration (cv) are found. The Ms and As both decrease from 1100 and 1150˚C to as low as -206˚C and -153˚C respectively, with increasing cv from 0.10 to around 0.30. When the number of valence electrons per atom is high (ev/a>7.50), the transformation temperatures show much less dependence on cv. High electron NiMnX (X=Ga, In, Al) Heusler alloys containing Mn (>30 at%) show high transformation temperatures at high cv values most likely due to anti-ferromagnetism of excess Mn which reduces the elastic moduli. The low valence electron group shows significantly lower transformation temperatures for their cv values compared to the main group. The influence of valence electron concentration is discussed on the basis of the variations of elastic moduli of the alloys as a result of composition change.